Filologia trasversale e recensioni (Prassi Ecdotiche della Modernità Letteraria, 2025)
This essay analyzes the premises, developments, and critical implications of the Osservatorio sulle Edizioni Critiche, an initiative launched by scholars at the University of Milan to foster interdisciplinary dialogue around philology understood as a pursuit of textual truth. Such truth, though rarely attainable, is treated as a methodological benchmark for distinguishing the historical and linguistic reality of a text from the interpretive layers added over time. The author proposes a notion of "transversal philology," capable of transcending disciplinary boundaries through the shared use of practices and tools, among which the critical review of scholarly editions plays a key role. However, the idea that such reviews could serve as a systematic tool for comparison has clashed with the current academic undervaluation of this form of contribution. While acknowledging changes in the academic landscape and the rise of new assessment criteria, the essay defends the formative, scientific, and dialogic value of reviewing as an exercise in critical reading, shared responsibility, and original contribution to philological knowledge. The reflection concludes with a call to preserve such instruments of awareness in an age marked by a crisis of truth and interpretation.
Keywords: Philology; Textual truth; Critical review; Scholarly edition; Interdisciplinarity